The Effect of Work Communication, Work Quality, and Career Development on Employee Job Satisfaction at PT Nasco (Indopine) in Deli Serdang Regency - Arya Novanda; Emi Wakhyuni; Chaerul Rizky (Journal of Management, Economic, and Accounting, 2026)
This study aims to examine the effect of work communication, work quality, and career development on employee job satisfaction at PT Nasco (Indopine) in Deli Serdang Regency. A quantitative approach with a descriptive research design was applied, and data analysis was performed using SPSS version 26. The population consisted of all 68 permanent and non-permanent employees, with the sample taken using a non-probability saturated sampling method, meaning the entire population was used as the sample. Partial test results indicate that work communication has a positive and significant effect on job satisfaction (t_calculated = 27.460 > t_table = 1.99773), work quality also has a positive and significant effect (t_calculated = 16.194 > t_table), and career development has a positive and significant effect as well (t_calculated = 10.587 > t_table). Simultaneously, all three independent variables positively and significantly influence job satisfaction, with F_calculated = 1,592.086 > F_table = 2.75 Hypothesis testing shows that the alternative hypothesis (H₁) is accepted and the null hypothesis (H₀) is rejected, both partially and simultaneously. The coefficient of determination (Adjusted R²) of 0.986 indicates that 98.6% of the variation in employee job satisfaction is explained by work communication, work quality, and career development, while the remaining 1.4% is influenced by other variables not examined in this study.